Wilson Disease: Novel Diagnostic and Therapeutic Approaches - Mariño, Zoe; Schilsky, Michael L. (Seminars in Liver Disease, 2024)
The Wilson disease (WD) research field is rapidly evolving, and new diagnostic and therapeutical approaches are expected to be change-gamers in the disease for the incoming years, after decades of slow changing options. Non–ceruloplasmin-bound copper assays for circulating bioavailable copper are being tested for use in monitoring therapy and may also help in the diagnosis of new cases of WD. Other diagnostic advances include the use of quantitative detection of ATP7B peptides in dried blood spots, a method that is being tested for use in the newborn screening for WD, and the use of metallothionein immunostaining of liver biopsy specimens to differentiate WD from other liver diseases. Ongoing and future trials of gene therapy and use of methanobactin are expected to restore biliary copper excretion from the liver, thus making a cure for WD a plausible therapeutic objective. With the aim of helping updating physicians, this review summarizes the novel methods for WD diagnosis and future therapies. Advancing understanding of the scientific advances that can be applied to WD will be critical for ensuring that our patients will receive the best current and future care.
Keywords: Wilson disease; research; diagnosis; treatment; copper